Histomorphological and Histochemical Studies on the Dorsal Buccal Gland of Sheep (Ovis aries) - Singh, A D; Jain, R K; Kumar, Pawan (Indian Journal of Veterinary Anatomy, 2012)
The present study was conducted on the dorsal buccal gland of ten healthy adult sheep of local mixed breed. Histologically, the gland was compound tubulo-alveolar being surrounded by less distinct capsule. The gland was sero-mucous with predominance of mucous alveoli. The mucous alveoli showed positive reaction to mucosubstances, glycogen, mucopolysaccharides, mucin and Sudanophilic lipids while serous cells were negative to all these histochemical reactions.